2006
DOI: 10.1007/s11420-005-0125-z
|View full text |Cite
|
Sign up to set email alerts
|

Are Postoperative Complications More Common with Single-Stage Bilateral (SBTKR) Than with Unilateral Knee Arthroplasty: Guidelines for Patients Scheduled for SBTKR

Abstract: A significant number of patients with degener-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(48 citation statements)
references
References 17 publications
1
46
1
Order By: Relevance
“…The mean age of the patients was 65 years in the study by Urban et al (11). In the present study, 51.6% of the patients were aged below 65 years and 48.4% were above 65 years, a finding similar to that reported in the aforementioned studies.…”
Section: Discussionsupporting
confidence: 91%
“…The mean age of the patients was 65 years in the study by Urban et al (11). In the present study, 51.6% of the patients were aged below 65 years and 48.4% were above 65 years, a finding similar to that reported in the aforementioned studies.…”
Section: Discussionsupporting
confidence: 91%
“…28 In addition, 1 study of in-hospital mortality found that 0.5% of patients who had BTKA died compared with 0.3% of patients who had UTKA. 29 In contrast, our study identified lower mortality among patients who had UTKA, with no significant difference between cohorts (0.3% in the BTKA group v. 0.1% in the UTKA group, p = 0.48). Although the literature predominantly reflects higher mortality in patients who had BTKA, many BTKA = bilateral total knee arthroplasty; CI = con dence interval; COPD = chronic obstructive pulmonary disease; Hb = hemoglobin; OR = odds ratio; SD = standard deviation; UTKA= unilateral total knee arthroplasty.…”
Section: Recherchecontrasting
confidence: 84%
“…However, despite potential advantages of the same-day approach, including exposure to the risks of anesthetic only once, one postoperative course of pain, reduced rehabilitation, and an earlier return to baseline function [10,11,23], the safety of same-day procedures has been questioned because of higher morbidity and mortality when compared with unilateral TKAs [15,22]. Several studies have attempted to compare the incidence of complications after same-day bilateral TKAs, staged bilateral TKAs, and unilateral TKAs using single institution databases, large administrative datasets, or meta-analyses [1,6,7,9,14,15,18,22,[26][27][28]. However, there are no randomized trials comparing the safety of these surgical strategies.…”
Section: Introductionmentioning
confidence: 99%
“…However, there are no randomized trials comparing the safety of these surgical strategies. Because of the diversity of study settings and designs, it is difficult to draw definitive conclusions [1,6,7,9,14,15,18,22,[26][27][28].…”
Section: Introductionmentioning
confidence: 99%